Apolipoprotein E variants, plasma lipids, lipoproteins and dysApolipoprotein E variants, plasma lipids, lipoproteins and dysβLipoproteinaemia during pregnancy in Zimbabwean women. - Tanyanyiwa, Donald Moshen (Division of Chemical Pathology, 2014)
Includes bibliographical references (leaves 117-138).